SMALLHOLDER FARMERS’ ADAPTATION TO RAINFALL VARIABILITY IN NORTHERN GHANA - Mustapha, Salisu; Iddrisu, Tijani Inusah; Adzawla, William (PEOPLE: International Journal of Social Sciences, 2020)
Irregular rainfall pattern pose challenges to smallholder farmers in Ghana, especially, those in the Northern Region, who risk losing their major source of livelihood as a result of the devastating impacts of climate change. To ensure food and livelihood security, smallholder farmers adopt indigenous and modern soil and water conservation strategies. This study therefore examined the influencing factors of adaptation to irregular rainfall pattern and the challenges therein. A cross sectional data of 140 households from five (5) randomly selected districts in the Northern region of Ghana was used. Results of a Negative Binomial Regression showed that access to extension services and credit positively influenced the number of adaptation strategies to irregular rainfall pattern. Also, quantity harvested, gender and age negatively influenced the number of adaptation strategies adopted by a farmer. Consistently, lack of credit was the first major constraint to climate adaptation among the farmers. The study recommends that extension services, credit facilities as well as education of smallholder farmers should be intensified to promote adaptation to the rainfall patterns in the region. Also, government’s effort is needed in developing irrigation facilities to aid smallholder farmers to offset the potential effects of climate change. Overall, this study provides suggestions to policy makers on how to improve climate adaptation in the region. Future studies should examine forms and effectiveness of climate change communication, since effective communication is imperative to the adoption of modern agricultural practices.